Variable periodic time operated fibre-coupled dosimetry system using Ag-activated RPL glasses with build-up. (April 2020) - Kurobori, Toshio; Yanagida, Yuka; Koguchi, Yasuhiro; Yamamoto, Takayoshi
Abstract: We report the demonstration of a variable periodic time operated fibre-coupled dosimetry system using Ag-activated phosphate glass based on radiophotoluminescent (RPL) phenomenon. In order to overcome the inevitable "build-up" effect occurring in RPL glasses during and after X-ray irradiation, pertinent experiments are designed and carried out. The RPL intensities for four successive sequences, namely, the pre-dose, X-ray exposure, build-up and optical bleaching processes, are examined for the orange and blue RPL bands. Build-up curves and corresponding build-up rates are measured for different excitation wavelengths, analytically evaluated, and compared with those of a real-time fibre plastic scintillation dosimetry system. In addition, the orange RPL signal dependence on temperature and variable interval is examined for three successive sequences. The quick response of the dosimetry system developed here to the on / off switching operations is confirmed using seven successive sequences. Highlights: New dosimetry system using radiophotoluminescent (RPL) phenomenon is developed . RPL intensities for four sequences for Ag-activated phosphate glass are examined . Build-up curves and rates were investigated for different excitation wavelengths . The excitation wavelength influences rising time and RPL intensity of the build-up .